2014
DOI: 10.1371/journal.pgen.1004518
|View full text |Cite|
|
Sign up to set email alerts
|

Requirements for Pseudomonas aeruginosa Acute Burn and Chronic Surgical Wound Infection

Abstract: Opportunistic infections caused by Pseudomonas aeruginosa can be acute or chronic. While acute infections often spread rapidly and can cause tissue damage and sepsis with high mortality rates, chronic infections can persist for weeks, months, or years in the face of intensive clinical intervention. Remarkably, this diverse infectious capability is not accompanied by extensive variation in genomic content, suggesting that the genetic capacity to be an acute or a chronic pathogen is present in most P. aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
357
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(397 citation statements)
references
References 55 publications
29
357
2
2
Order By: Relevance
“…Similarities have been observed in the active biosynthetic pathways of P. aeruginosa in the CF lung and murine surgical wound infections [127]. This suggests that (i) catabolite metabolism is shared between certain infection sites and (ii) other factors, such as host-inflammatory responses, may be the cause of infection chronicity.…”
Section: In Vivo Conditions In Vitro Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…Similarities have been observed in the active biosynthetic pathways of P. aeruginosa in the CF lung and murine surgical wound infections [127]. This suggests that (i) catabolite metabolism is shared between certain infection sites and (ii) other factors, such as host-inflammatory responses, may be the cause of infection chronicity.…”
Section: In Vivo Conditions In Vitro Methodssupporting
confidence: 57%
“…Nutritional cues similar to those of expectorated CF sputum have been incorporated into a synthetic CF sputum media (SCFM) that approximates P. aeruginosa gene expression to that observed in expectorated CF sputum [120]. Two noteworthy points of this study are (i) the lack of key components observed in CF sputum (notably DNA, fatty acids, N-acetyle glucosamine, and mucin) and (ii) the inability of the methods used (RNA-seq) to correctly predict fitness requirements [121][122][123][124][125][126][127]. A follow up study rectified these issues, incorporating these components into SCFM.…”
Section: In Vivo Conditions In Vitro Methodsmentioning
confidence: 99%
“…First, selection for phage resistance could be weaker in polymicrobial communities due to a competition‐mediated reduction in the focal pathogen density and relatively higher pleiotropic costs of adaptation. Competition could thus enhance the phage efficacy when treating acute CF and burn infections that are commonly co‐infected by QS signalling P. aeruginosa , S. aureus and S. maltophilia (Harrison, 2007; Turner et al., 2014). However, in contrary, P. aeruginosa resistance evolution to phages could be a more severe problem in chronic polymicrobial CF infections that are often dominated by P. aeruginosa mutants that have lost QS signalling ability during the long‐term adaptation (Andersen et al., 2015; Marvig et al., 2014; Smith et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium Pseudomonas aeruginosa is an opportunistic pathogen that commonly infects many immunocompromised patients including cystic fibrosis (CF) and burn victim patients (Harrison, 2007; Turner, Everett, Trivedi, Rumbaugh, & Whiteley, 2014). P. aeruginosa is often characterized by multidrug resistance to conventional antibiotics (Strateva & Yordanov, 2009), and hence, the development of novel phage therapy treatments could potentially help a large number of patients (Harper & Enright, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from each mutant pool largely as described previously (83). An aliquot (1-ml glycerol stock) was resuspended in 1 ml 1ϫ buffer A (84) plus 0.1% SDS and 0.1% sodium deoxycholate, transferred to a Lysing Matrix B 2-ml tube (MP Biomedicals), homogenized in a Mini-Beadbeater (BioSpec), and digested overnight at 55°C with 1 mg/ml proteinase K. DNA was then extracted with 1 ml 25:24:1 phenol-chloroform-isoamyl alcohol (pH 8.0), purified from the aqueous phase by isopropanol precipitation, washed with 75% ethanol, and dissolved in 500 l distilled water (diH 2 O).…”
Section: Methodsmentioning
confidence: 99%